Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Kepuasan Nasabah pada LPD Desa Adat Sanding Tampaksiring Gianyar - Wayan Krishna Bintang Mahardika; I Gst. Ayu Wirati Adriati (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of service quality and trust on customer satisfaction. The sample in this study is customers of LPD Desa Adat Sanding Tampaksiring Gianyar totaling 98 respondents. The data analysis techniques use validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, F test, and t test. From the results of the study, it is obtained that service quality has a positive and significant effect on customer satisfaction, trust has a positive and significant effect on customer satisfaction, and service quality and trust have a significant effect on customer satisfaction. The magnitude of the influence of the independent variables on customer satisfaction is 60%. The suggestion that can be given by the researcher is that LPD Desa Adat Sanding Tampaksiring Gianyar should always supervise employees in providing services, so that employees try to be friendly in providing services, improve employee abilities in building customer trust by providing training to employees, and improve the quality of services.